Arabic Placement Test (APT) and achievement test: a comparison study on teachers’ and students’ perspectives - Hashim, Najmiah; Arshad, Mastura; Samat, Nur Arifah; Muhammad, Ilyani Syiham; Mustapai, Mohd Zulhisyam; Abdul Jabbar, Muhammad Bahari (Centre of Foundation Studies, International Islamic University Malaysia, 2021)
This study is conducted as an attempt to change the end-of-semester examination from Arabic Placement Test (APT) to an achievement test which involves Quranic Language courses of elementary levels in the Centre for Foundation Studies (CFS), IIUM. The APT has been used as the end-of-semester examination for 9 years since 2012. Based on APT results analysis for 3 consecutive years, it is found that there are a lot of drawbacks which affect courses, as well as teachers’ and students’ performances. This quantitative study aims to collect teachers’ and students’ perceptions on the application of achievement test as the end-of-semester examination. A pilot study was conducted in semester 2, 2018/2019 and a sample of achievement tests was designed and assigned to 62 respondents. They were given a set of questionnaires in order to get their perspectives on using the test as the end-of-semester examination and another set of questionnaire were prepared and distributed to all teachers in Department of Quranic Language (QLD), CFS, to study their perspectives on the application of the achievement test as the end-of-semester examination. As a result, 100% of QLD teachers agreed that the achievement test was more effective than APT to be the end-of-semester examination while 74.2% of students believed that the achievement test was more effective than APT.